'Hustler lives' and digital dilemmas in Kenya: Young men negotiating work opportunities, life aspirations and mobile phone use. (1st June 2017) - Tufte, Thomas
This article explores the livelihoods and media uses of young men in rural, urban and peri-urban Kenya, enquiring into how these young men use digital technologies, mobile phones in particular, in the context of constantly and quite rapidly changing livelihoods. It is a media ethnographic case study offering a gendered perspective upon the lives of male youth in Kenya. Kenya is a country branded as being digitally innovative, disruptive, entrepreneurial and developing new opportunities for Kenyan economic development and for the citizens of Kenya (ICT Authority 2014). By unpacking the socio-economic organization of everyday life and the quotidian use of mobile phones amongst mainly low-income young men in Uasin Gishu County in Rift Valley, this study enquires into the strategies applied by these young men in pursuing their aspirations for a better life. How do they navigate in the context of a rapidly and profoundly changing society informed by policies and discourses of digital innovation? It is a context where mobile phones by government are considered spearheads of digital innovation, disruption and entrepreneurship, but where the everyday usage reveals deeper complexities and contradictions. From reviewing the experiences of 36 young men I have identified work-oriented profiles of three young men. Their profiles, albeit unique, resonate with many of the persistent features of all 36, in how they negotiate work opportunities and media uses in their aspirations for a good life. The three profiles I have identified are (1) the digital entrepreneur; (2) the urban casual worker; and (3) the university student and opinion leader.